Diagnosis of exercise-induced sronchoconstriction in Swimmers: Context matters - Leahy, M. G.; Peters, C. M.; Geary, C. M.; Koehle, M. S.; McKenzie, D. C.; Brotherhood, J.; Sheel, A. W. (Medicine & Science in Sports & Exercise, 2020)
Swimmers have a high prevalence of exercise-induced bronchoconstriction (EIB), which may be associated with repeated exposure to chlorinated pool water. The eucapnic voluntary hyperpnea (EVH) test is used to diagnose EIB; however, it fails to replicate the environmental conditions experienced by swimmers. The relationship between the composition of the EVH inspired gas and the development of EIB from swim exercise remains unclear.